2021
DOI: 10.3390/sym13030492
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a High-Reliability Multicriteria Trust Evaluation Model with Task Role-Based Access Control for Cloud Services

Abstract: Cloud data storage is revolutionary because it eliminates the need for additional hardware, which is often costly, inconvenient, and requires additional space. Cloud data storage allows data owners to store large amounts of data in a flexible way and at low cost. The number of online cloud storage services and their consumers has therefore increased dramatically. However, ensuring the privacy and security of data on a digital platform is often a challenge. A cryptographic task-role-based access control (T-RBAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The need for such an approach is important to verify the results obtained from the previous steps of the research. The research has shown that the use of quality tools helps to identify the potential causes of the problem under analysis [27,28]. When solving a problem, it is important to find out the real cause of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…The need for such an approach is important to verify the results obtained from the previous steps of the research. The research has shown that the use of quality tools helps to identify the potential causes of the problem under analysis [27,28]. When solving a problem, it is important to find out the real cause of the problem.…”
Section: Discussionmentioning
confidence: 99%
“…Any type of trust management service is vulnerable to a variety of attacks [31]. These attacks have the potential to either enhance or destroy the reputation of a specific entity [32,33]. In order to build an accurate and secure trust model system, we focus on implementing various metrics to prevent these attacks, which enables us to create a stable, reliable, and accurate trust model framework.…”
Section: Comparison Of Security and Accuracymentioning
confidence: 99%
“…The security threats that threaten a TMS may sometimes arise from the consumers of the service themselves. Information concerning a user's experience can be obtained from feedback received [20] [21]. However, it can be very difficult to determine which kinds of activities are malicious.…”
Section: Taxonomy Of Cloud Service Reputation Attacksmentioning
confidence: 99%
“…The credibility of reputation systems can be damaged by the entities involved in those systems, intentionally or unintentionally, separately or together with others, based on the given application and social environment of the reputation system. There are basically two types of trust: recommendation trust (RT), which is the trust of the service provider in other service providers, and interaction trust (IT), which is the trust of the service provider in the consumers regarding the use of their services [20] [21]. Each type has many categories into which reputation attacks or misbehaviors of entities can be classified.…”
Section: Taxonomy Of Cloud Service Reputation Attacksmentioning
confidence: 99%
See 1 more Smart Citation